Carbon Monoxide Axidation Over Pt/Y-Alumina Catalyst - Triyono Triyono; Chairil Anwar (Testing Center for Oil and Gas LEMIGAS, 1998)
Oxidation of CO has been studied on Pt/y-alumina catalyst. The catalyst was produced by impregnating y-alumina with hexachloroplantic acid solution, calcined, oxidized and reduced at the optimum condition. Catalyst was characterized by nitrogen sorption measurement and scanning electron microscope (SEM). By optimization of calcination, oxidation and reduction on the catalyst preparation, a residual serface area of 129.14 mÂ²/gram was obtained. The resulting catalyst has a high activity for the conversion of CO to COâ‚‚.